THE POWER OF AI IN EDUCATION: EXPLORING CHATGPT'S IMPACT ON STUDENTS' LEARNING - Aryani, Vera; Sari, Ika Lusiana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study investigates the impact of ChatGPT usage on students' learning in the Business Administration department at Politeknik Negeri Pontianak. Using a quantitative cross-sectional survey design, data was collected from a sample of active students and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM). The measurement model confirmed the reliability and validity of the constructs. The structural model revealed that ChatGPT usage had significant positive effects on critical thinking skills (β = 0.654, p < 0.001), learning efficiency (β = 0.748, p < 0.001), and material comprehension (β = 0.703, p < 0.001), explaining 42.8%, 56%, and 49.4% of the variance, respectively. However, ChatGPT usage did not significantly impact academic achievement (β = -0.102, p = 0.125). These findings suggest that while ChatGPT can enhance critical thinking, streamline learning, and facilitate deeper understanding, its direct influence on grades and overall performance is more complex. Educators should carefully consider course goals and contexts when implementing ChatGPT. Future research could explore moderating factors, long-term effects, and the evolving role of AI in education to harness its potential in supporting student learning experiences.